Biological Barriers in Drug Delivery - Vaidya, Sunita N. (Asian Journal of Pharmaceutics (AJP), 2024)
The concept of biological barriers to drug delivery is crucial for the development and optimization of pharmaceutical treatments. These obstacles represent complex and dynamic physiological systems within the human body that must be navigated by drugs to reach the intended target sites. Key biological barriers include blood-brain barrier (BBB), gastrointestinal (GI) barrier, placental barrier during pregnancy, and immune system. The BBB is a selective interface created by endothelial cells present in the blood arteries of the brain that restricts the flow of many medications, making it difficult to treat neurological illnesses. However, because the medicine comes into contact with different enzymes and transporters in the digestive system, the GI barrier may have an impact on drug absorption and bioavailability. In pregnancy, the placental barrier protects the developing fetus from potential harm, but it can also limit access to the fetal circulation of drugs. While the immune system is primarily responsible for protecting the body from foreign invaders, it can also act as a facilitator and a barrier to drug delivery. Immunotherapies use the immune system to target cancer cells, but the immune response may also lead to drug clearance or side effects. Understanding and addressing these biological barriers is crucial for drug design, formulation, and delivery strategies. Researchers and pharmaceutical companies continue to innovate to optimize drug delivery systems, enabling drugs to overcome these challenges and achieve their intended therapeutic targets effectively and safely. The development of novel drug delivery technologies and strategies promises to provide more precise and effective treatments for a wide range of diseases.